A framework for sustainable mobile learning in schools. (25th July 2012) - Ng, Wan; Nicholas, Howard
Abstract: While there are studies that have looked at the implementation of mobile learning in educational institutions, particularly the identification of issues encountered, few studies have explored holistically the elements that sustain mobile learning. This study dissects the findings of a longitudinal study of a secondary school adopting a personal digital assistant programme and proposes a person‐centred sustainable model for mobile learning.